Efeito da temperatura de superenvelhecimento no recozimento contínuo nas propriedades mecânicas do aço TRIP780 - Rafael Ricardo Magalhães (2019)
In this work was studied the effect of the start and end temperatures of the overaging (SE) of a continuous annealing cycle on the microstructure and the mechanical properties of a low carbon TRIP steel with a minimum strength limit of 780MPa to determine the best conditions in terms of mechanical properties. Samples of 1.10mm thickness were annealed until 800°C, at the Usiminas research Center, using the Gleeble equipment. After this process, the samples were cooled to the start temperatures overaging (SEi) at 440°C, 420°C, 400°C. Then, the samples remained at those temperatures for a period of 5min or were cooled to temperatures ranging from 440°C to 320°C using low cooling rates of 1x10-1°C/s to 3.8x10-1°C/s. These temperatures were chosen in order to be applicable in the industrial process with current equipment. After the annealing cycles simulations, all samples were submitted to tensile, metallography, X-ray diffraction and dilatometry tests for the microstructural evaluation and the mechanical properties of the steel. The microstructures presented variable volume of ferrite, bainite, retained austenite and small portion of martensite. All conditions reached a minimum strength of 780MPa, it is possible to highlight the conditions for temperature SEi of 400°C where it presented the best results of mechanical properties and typical characteristics of TRIP steels.